The triple-shape memory effect in NiTi shape memory alloys - Tang, Cheng (2013)
We report two approaches to realize the triple-shape memory effect (SME), i.e., returning to the original shape from the temporary shape through one intermediate shape in a gradual/step-by-step heating induced recovery, in NiTi shape memory alloys (SMAs). In the programming process (which is to fix the temporary shape) in both approaches, the deformation is uniform throughout the whole length of the SMA samples without introducing any permanent change in the material properties. The requirements/conditions for this phenomenon and the underlying mechanisms are presented, together with experimental verifications. As revealed, with this technique, we are now able to achieve 'the material is the machine' for well controlled multi-positional maneuvers in SMAs.